PENGARUH BANTUAN SOSIAL USAHA EKONOMI PRODUKTIF DAN KELOMPOK USAHA BERSAMA TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT DI KABUPATEN SUMBAWA BARAT - HANISAH, HANISAH; UMAR, UMAR; SUHARI, LILI (GANEC SWARA, 2023)
The purpose of this study is to determine the implementation of the Productive Economic Enterprises (UEP) and Joint Business Groups (KUBE) programs in improving the social welfare of people with welfare problems in West Sumbawa Regency and to analyze the level of effectiveness of the Joint Business Groups program in improving the social welfare of people with welfare problems in West Sumbawa Regency.  This research uses mixed methods (combined methods) qualitative methods to determine the implementation of the Productive Economic Enterprises and Joint Business Groups programs in improving the social welfare of people with welfare problems in West Sumbawa Regency and quantitative methods to analyze the effectiveness of the Productive Economic Enterprises Joint Business Groups program in improving community welfare in West Sumbawa Regency. The results of the research show that the implementation of the Productive Economic Enterprises and Joint Business Groups programs in improving the social welfare of people with welfare problems in West Sumbawa Regency can be concluded, among others, UEP and KUBE are government programs in the form of business assistance to the people of West Sumbawa which have been implemented well by the West Sumbawa Regency Social Service. The UEP and KUBE programs in the West Sumbawa community are implemented procedurally in accordance with existing regulations, both from the process of submitting applications for assistance, assistance and assessment of beneficiaries. With N = 17, from the t table above, the t table value is 0.689, the significance value of the table is 0.007 so that the significance value is 0.007 < 0.689 or the value of t count < t table so that it can be concluded that the Productive Economic Enterprises (UEP) and Joint Business Groups (KUBE) social assistance program is effective in improving community welfare in West Sumbawa Regency.